Participation in ICT-based market information projects, smallholder farmers' commercialisation, and agricultural income effects: findings from Kenya. Issue 8 (16th November 2020) - Okello, Julius J.; Kirui, Oliver K.; Gitonga, Zachary M.
ABSTRACT: Agricultural projects that use information and communication technologies (ICT) to provide market information have increased considerably in developing countries in the last decade. These projects aim to strengthen smallholder farmers' linkage to input and output markets. This article examines the impact of such projects on smallholder farmers' input and output commercialisation, and household income, using propensity score matching technique and data collected from farmers in Kenya. The study finds that participation in ICT-based projects increases farmers' participation in input and output markets, and their household income. The article highlights the implications of these findings for ICT policy and practice.